ABCB1 Gene Polymorphisms and Their Contribution to Cognitive Decline in Mild Cognitive Impairment: A Next-Generation Sequencing Study - Šerý, Omar; Sheardová, Kateřina; Dziedzinska, Radka; Zeman, Tomáš; Vyhnálek, Martin; Marková, Hana; Laczó, Jan; Lochman, Jan; Vrzalová, Kamila; Balcar, Vladimir J; Hort, Jakub (The journals of gerontology. Series A, Biological sciences and medical sciences, 2025)
The ABCB1 gene, encoding the ATP-dependent translocase ABCB1, plays a crucial role in the clearance of amyloid-beta (Aβ) peptides and the transport of cholesterol, implicating it in the pathogenesis of Alzheimer's disease. The study aims to investigate the association between polymorphisms in the ABCB1 gene and cognitive decline in individuals with mild cognitive impairment (MCI), particularly focusing on language function. A longitudinal cohort study involving 1 005 participants from the Czech Brain Aging Study was conducted. Participants included individuals with Alzheimer's disease, amnestic MCI, non-amnestic MCI, subjective cognitive decline, and healthy controls. Next-generation sequencing was utilized to analyze the entire ABCB1 gene. Cognitive performance was assessed using a comprehensive battery of neuropsychological tests, including the Boston Naming Test and the semantic verbal fluency test. Ten ABCB1 polymorphisms (rs55912869, rs56243536, rs10225473, rs10274587, rs2235040, rs12720067, rs12334183, rs10260862, rs201620488, and rs28718458) were significantly associated with cognitive performance, particularly in language decline among amnestic MCI patients. In silico analyses revealed that some of these polymorphisms may affect the binding sites for transcription factors (HNF-3alpha, C/EBPβ, GR-alpha) and the generation of novel exonic splicing enhancers. Additionally, polymorphism rs55912869 was identified as a potential binding site for the microRNA hsa-mir-3163. Our findings highlight the significant role of ABCB1 polymorphisms in cognitive decline, particularly in language function, among individuals with amnestic MCI. These polymorphisms may influence gene expression and function through interactions with miRNAs, transcription factors, and alternative splicing mechanisms.
Keywords: senioři; longitudinální studie; Cognitive Dysfunction; senioři nad 80 let; jednonukleotidový polymorfismus; Neuropsychological Tests; Alzheimer’s disease; DNA polymorphisms; Česká republika; mužské pohlaví; Alzheimer Disease; Czech Republic; ATP Binding Cassette Transporter, Subfamily B; ATP-dependent translocase; Aged, 80 and over; ženské pohlaví; neuropsychologické testy; Humans; High-Throughput Nucleotide Sequencing; ATP-binding cassette transporters; kognitivní dysfunkce; vysoce účinné nukleotidové sekvenování; Language decline; P-glykoproteiny; Alzheimerova nemoc; Longitudinal Studies; Female; Aged; lidé; Male; Polymorphism, Single Nucleotide